Thirty years of success - The, Star (The Star, 2014)
OFFICIALLY established on Feb16,1984,Universiti Utara Malaysia (UUM) is the sixth public university in the country and the only one set up specifically for business and management education. Now in its 30th year, UUM looks back on its humble beginnings and looks forward to even greater triumphs and achievements.